Infak dan Kesejahteraan: Studi Kasus Dampak Berinfaq Bagi Munfiq pada Civitas Akademika Fakultas Ekonomi dan Bisnis Universitas Brawijaya - Tufail Rosyad Abdi; Aminullah Achmad Muttaqin (STES Islamic Village, 2020)
Infaq is a form of ibadah that has 2 dimensional forms, firstly is horizontal dimension and secondly is vertical dimension. In the first dimension, infaq is manifested as a form of servant’s obedience to the Creator. Secondly, it is showed as a form of caring to others. In Islamic Teaching, infaq as a form of ibadah is not only beneficial for recipients but also for the munfiq (donator) itself. Therefore this study aims to investigated the impact of infaq for the munfiq. The variables used in this study are the amount of infaq expenditures, income, age, marital status and faith. While the research method used in this research is quantitative with multiple linear regression analysis tools. The results obtained from this study indicate that infak has a significant effect on the welfare of the munfiq individual, as well as the income, age and faith variables. Meanwhile, the variable amount of infaq expenditure and marital status did not affect the welfare of the individual munfiq.